Silicone-incorporated nanoporous cobalt oxide and MXene nanocomposite-coated stretchable fabric for wearable triboelectric nanogenerator and self-powered sensing applications - Rahman, M. Toyabur; Rana, S. M. Sohel; Salauddin, M.; Abu Zahed, M.; Lee, Sanghyun; Yoon, Eui-Sung; Park, Jae Yeong (Elsevier BV, 2022)
Triboelectric nanogenerators (TENGs) provide a desirable solution to alleviate the expanding energy supply concerns in the development of self-powered wearable devices and sensors. Herein, a novel wearable, stretchable multifunctional double-layered TENG is fabricated by using a metal-organic framework-derived nanoporous cobalt oxide (NPCO)/silicone and MXene/silicone nanocomposite. The excellent nanoporosity of NPCO induces high charge accumulations that promote the electronegativity of the nanocomposite by fourfold. In addition, MXene/silicone with bifunctionality (charge trapping and charge transport) is incorporated into the intermediate layer to improve the charge trapping capability and electronegativity of the nanocomposite by nine times. Facile, hierarchical fabric-assisted micro/nanostructures on the nanocomposite are conceived to increase hydrophobicity and water resistivity. Conductive knitted fabric is employed as a flexible electrode to obtain high stretchability (230 %) and robustness. Owing to the synergistic effect of the optimized nanocomposite, the fabricated TENG delivers a high power density (10.4 W/m2), which is approximately 23 times higher than the pure silicone-based TENG. By exploiting the outstanding sensitivity (5.82 V/kPa), the TENG reveals an extraordinary self-powered biomotion sensor, and its practical applications in a foot pressure distribution sensor array and a self-powered wearable keyboard. This work provides new insights into the design of highperformance TENGs with high sensitivity and durability and facilitates their applications in biomechanical energy harvesting and self-powered wearable sensors.